Student's Conception about Friction Force Direction in Physics Education Sebelas Maret University - Puspita Septim Wulandari; C Cari; Nonoh Siti Aminah (Journal of Physics: Theories and Applications, 2017)
The student's conception of friction force direction on objects is different. Student’s conceptions are important to improve the next learning process. The aim to the research was to know student’s conception about friction force direction. This research was a qualitative descriptive. Samples consisted of  33 students from Physics Education UNS semester 1 who have not obtained the material friction in the lecture. Data collected through test and intervie. Data were analyzed by reduction, presentation, conclusion and verification. Based on the result of student conception showed the average of 82,82% student can describe the direction of friction force on objects with translational motion, 18,18% student can describe the direction of friction force on objects with translational and rotation motion inclane and all students can not describe the direction of friction force on bicycle wheels.